Tech-Driven HRM Framework: Future-Proofing Employee Rights, Blockchain Streamlined Compliance, SSD assembled Data Integrity securing Entrepreneurial Workforce - Andalib, Tarnima Warda; Hassan, Dauwood Ibrahim; Azizan, Noor Azlinna; Arif, Nabil Bin; Ramayah, T (Journal of Posthumanism, 2025)
This research investigates how using blockchain technology in HRM combines improved regulatory adherence with worker rights protection. The research employed qualitative methodology within an ontological paradigm by conducting a Systematic Literature Review together with case study investigations of eighty-seven (87) large-scale manufacturing companies' respondents in twelve (12) organizations. NVivo coding revealed important themes, including organizational adjustments towards entrepreneurship, HRM compliance standards, and technical advancements. Soft systems methodology underpinned the creation of a Tech-driven HRM framework, which received validation by means of triangulation. Standards derived from UDHR, ILO conventions and Bangladesh Labour Act (BDL 2006) form the basis of the framework that drives continuous workforce growth while enhancing entrepreneurial development and employee involvement throughout different business sites.